25-hydroxyvitamin D Serum Level and Risk of Knee Osteoarthritis in the Elderly - Putri, Indira Ayu; Kurniawan, Felicia; Sahusilawane, Isadora Gracia; Hananta, Linawati (Althea Medical Journal, 2025)
Background: Osteoarthritis (OA) is a degenerative joint disease that commonly affects the elderly, particularly in the knees. The OA may lead to chronic pain, physical limitations, depression, and significantly impact an individual's ability to participate in social, occupational, and community activities, ultimately reducing quality of life. Vitamin D has been suggested as a factor that may help reduce the risk of knee OA in older adults. This study aimed to investigate the relationship between 25-hydroxyvitamin D levels and the risk of knee OA among elderly.Methods: This cross-sectional study involved elderly residents of a nursing home in North Jakarta, Indonesia. Data was collected through interviews and physical examinations of both knees following the American Rheumatism Knee OA diagnostic criteria. Participants who met these criteria were classified as high-risk for knee OA. Blood samples were taken to measure 25-hydroxyvitamin D (25(OH)D) levels using an enzyme-linked immunosorbent assay. The Chi-square test was used for bivariate analysis.Results: Of the 48 participants involved, the majority were female (64.6%) and aged between 70-79 years (47.9%). A total of 22.9% of participants were classified as 25(OH)D insufficient and 25% were deficient. Interestingly, 62.5% were at high risk of knee OA. There was a significant association between 25(OH)D levels and the risk of knee OA (p=0.031).Conclusions: The 25(OH)D serum level has a significant association with the risk of knee OA. Increasing sunlight exposure through daily outdoor activities and considering vitamin D supplementation can help mitigate the risk of knee OA, thereby improving bone health and preventing OA in the elderly.